Evaluation of change in knowledge and attitude about noise and its effect on hearing: post awareness programme among adolescents in Varkala, Thiruvananthapuram district, Kerala - Vijayakumar, Sajay Sajana; Srividya, A.; Babu, Praveena (International Journal Of Community Medicine And Public Health, 2024)
Background: There are significant literature evidence across the globe and in India, regarding the effects of recreational noise exposure among young adults and college students, but there is a dearth of literature support regarding its effects among the students of senior grade studying in Indian subcontinent. Since the awareness among school students help in the early preventive measures and hearing conservation, studies must focus on these population to reduce the burden of recreational noise-induced hearing loss on our future generation. This study aims to evaluate the change in knowledge and attitude about noise and its effect on hearing: Post awareness programme among adolescents in Varkala, Thiruvananthapuram district, Kerala. Method: A survey was conducted among the school students within the age group 16-18 years. A questionnaire containing questions related to knowledge and attitude towards noise and its effect on hearing was developed and distributed to the students prior to and after an awareness program making use of a visual awareness material. Wilcoxon signed rank test was used for pre and post comparison. Results: The p value of each aspect related to the knowledge and attitude is less than the significance level, so we can say that there is a significant change in the level of knowledge and attitude after the awareness program. Conclusions: The study highlighted low pre-awareness levels among participants regarding noise's impact on hearing. The awareness program effectively improved understanding, emphasizing its importance for all age groups in dispelling misconceptions and fostering positive attitudes.